1998
DOI: 10.1063/1.476294
|View full text |Cite
|
Sign up to set email alerts
|

Collision-induced activation of the β-hydride elimination reaction of isobutyl iodide dissociatively chemisorbed on Al(111)

Abstract: The collision-induced activation of the endothermic surface reaction of isobutyl iodide chemisorbed on an Al(111) surface is demonstrated using inert-gas, hyperthermal atomic beams. The collision-induced reaction (CIR) is highly selective towards promoting the β-hydride elimination pathway of the chemisorbed isobutyl fragments. The cross section for the collision-induced reaction was measured over a wide range of energies (14–92 kcal/mol) at normal incidence for Ar, Kr, and Xe atom beams. The CIR cross section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The surface area on which an atomic impact yields a desorption event per adsorbed molecule (either H or AlH 3 ) is the desorption cross-section, Q D . Ceyer et al described this relationship thoroughly in the context of a now classic study of the methane/Ni(111) system. ,, Following that work, the cross section for desorption as a function of the collision energy, flux of the beam (oriented normal to the surface), and the surface coverage can be written as where E i is the energy of the incident beam, F B is the total flux in atoms/cm 2 , q ( t ) is the time dependent surface coverage, and t is the time of exposure to the incident beam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface area on which an atomic impact yields a desorption event per adsorbed molecule (either H or AlH 3 ) is the desorption cross-section, Q D . Ceyer et al described this relationship thoroughly in the context of a now classic study of the methane/Ni(111) system. ,, Following that work, the cross section for desorption as a function of the collision energy, flux of the beam (oriented normal to the surface), and the surface coverage can be written as where E i is the energy of the incident beam, F B is the total flux in atoms/cm 2 , q ( t ) is the time dependent surface coverage, and t is the time of exposure to the incident beam.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments for this study were performed in a three-stage UHV chamber that has been described in detail previously. , The first two stages of the chamber are used for beam generation. The beam is formed by a constant adiabatic expansion of the gas from a 25 mm molybdenum aperture.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 The CID of NH 3 and C 2 H 4 from Pt(111) was reported by Levis and co-workers, 5,6 O 2 from Pt(111) by Kasemo et al, 13 O 2 from Ag(110) by Rocca and co-workers, [10][11][12] Xe from Pt(111) by Rettner et al, 8a Ar from Ar covered Ru(001) by Head-Gordon et al, 8b N 2 from Ru(001) by Romm et al, 9 and water from Ru(001) by Asscher and coworkers. 7 Collision induced dissociation of adsorbed species was reported so far in the case of CH 4 on Ni(111), when energetic Xe atoms striked this surface to produce adsorbed methyl and hydrogen as a competing channel to the CID of methane, Ceyer et al 14,15 In addition, experiments have demonstrated the possibility for intramolecular, Nuzzo et al, 16 and bimolecular (CO oxidation to CO 2 ), Kasemo et al, 17 reactions induced by hyperthermal projectiles. Collisions of rare gas atoms on a hydrogen saturated Ni(111) resulted in a collision induced transition of surface hydrogen into subsurface atoms, as reported by Ceyer and co-workers.…”
Section: Introductionmentioning
confidence: 95%
“…Chemisorption occurs through bond formation. One way of enhancing this can be direct collisional activation; however, more importantly, chemisorption can be enhanced by precursor-mediated adsorption, where the molecule is first trapped in a weakly bound physisorbed state, which is a precursor for the formation of chemical bonds. , In this case, impinging water molecules get trapped into a shallow physisorption well, dominated by van der Waals interactions and static charge on the surface. These interactions are not sufficiently strong to fix the water molecule at the initial adsorption sites and the trapped precursor can migrate over the surface.…”
Section: Introductionmentioning
confidence: 99%